Specifying and verifying event-based fairness enhanced systems - SUN, Jun (Institutional Knowledge at Singapore Management University, 2008)
Liveness/Fairness plays an important role in software specification, verification and development. Existing event-based compositional models are safety-centric. In this paper, we describe a framework for systematically specifying and verifying event-based systems under fairness assumptions. We introduce different event annotations to associate fairness constraints with individual events. Fairness annotated events can be used to embed liveness/fairness assumptions in event-based models flexibly and naturally. We show that state-of-the-art verification algorithms can be extended to verify models under fairness assumptions, with little computational overhead. We further improve the algorithm by other model checking techniques like partial order reduction. A toolset named Pat has been developed to verify fairness enhanced event-based systems. Experiments show that Pat handles large systems with multiple fairness assumptions.